THE PLACE OF LEGAL NORMS ON THE PROTECTION OF THE ENVIRONMENT IN THE MILITARY AND DEFENSE FACILITIES IN THE SYSTEM OF ENVIRONMENTAL LAW (Journal of actual problems of jurisprudence, 2019)
The legal institute of preservation of the environment on military and defensive objects takes an independent place in system ofthe modern ecological right and is located in the Especial part of the ecological right. The given institute is difficult and complexinstitute of the right.